Team Cohesion and Performance Satisfaction among College’s Players: Mediating Role of Effective Communication - Tehzin Aslam; Ishrat Naheed; Rehmatullah; Saman Gul (Dialogue Social Science Review (DSSR), 2025)
Team Cohesion is an essential determinant of athlete satisfaction, but the pathways linking this variable to performance satisfaction in contexts like Pakistani collegiate sports are still unknown. Communication is hailed as the possible mediator. Principal Objective: This study was designed to explore whether effective communication could mediate the relationship between team cohesion and performance satisfaction of college athletes in Bhakkar District, Pakistan. Research Method: Using a cross-sectional survey of 283 athletes (stratified random sampling from 18 colleges), validated scales: Team Cohesion (Carron et al., 2002; α=0.85), Communication Effectiveness (Clampett et al., 1996; α=0.78), and Performance Satisfaction (Hays et al., 2009; α=0.82), were then administered. Mediation and binary logistic regression (satisfaction dichotomized: high/low) were analyzed. Results: Communication fully mediated the relationship between cohesion and satisfaction (indirect effect: β=0.2585, 95% CI [0.1940, 0.3243]). Cohesion directly predicted satisfaction (β=0.2646, p <.001), but 49.4% of its total effect (β=0.5232, p<.001) operated via communication. Logistic regression confirmed cohesion (OR=3.21, p<.001) and communication (OR=4.07, p<.001) as robust predictors of high satisfaction. Keywords: Team cohesion; Performance satisfaction; Communication mediation; Collegiate athletes; Pakistan.